Chemical investigation of Fe3+/Nb5+-doped barium titanate ceramics - L. Srisombat (2018)
Renewed interest in the perovskite ferroelectric barium titanate (BaTiO3) has been driven by the introduction of large recoverable electrostrain in doped BaTiO3-based materials. Our previous work demonstrated that the potential for high-performance in Pb-free ferroelectrics based on BaTiO3was confirmed in Fe3+/Nb5+-doped BaTiO3systems. It is well documented that the electronic behavior of BaTiO3is intimately related to the chemical state of the constituents. However, information regarding the chemical states of the ions of the Fe3+/Nb5+-doped BaTiO3ceramics is currently unavailable. Consequently, this study describes the chemical state of sintered hybrid Fe3+/Nb5+-doped BaTiO3ceramics, compared with undoped BaTiO3ceramics derived from the same processing. Analysis by X-ray photoelectron spectroscopy (XPS) showed that the binding energy of Ti indicates the presence of more than one component of Ti within the doped BaTiO3ceramics, but only one component of Ti within the undoped BaTiO3ceramics. Unlike Ti, the XPS spectra indicates that more than one type of barium and oxygen species exist in both undoped and doped BaTiO3ceramics. © 2012 Elsevier Ltd and Techna Group S.r.l.